High-pressure phase equilibrium data for systems involving carbon dioxide, globalide, ε-caprolactone, poly(globalide-co-ε-caprolactone) and dichloromethane - Dutra A.C. (2024)
© 2023 Elsevier B.V.The growing interest in producing biocompatible polymers, free of any kind of toxic residues, increasingly encourages the development of researches on clean processes. The use of supercritical carbon dioxide, replacing organic solvents, has shown to be a green alternative to traditional polymerization processes. Aiming at providing fundamental information to conduct polymerization reactions in supercritical carbon dioxide, this work reports experimental phase equilibrium data for the quinary system involving carbon dioxide, globalide, ε-caprolactone, poly(globalide-co-ε-caprolactone) and dichloromethane. The experiments were performed using a variable-volume view cell over the temperature range from 313.15 to 343.15 K, and different mass fractions of carbon dioxide in relation to monomers and copolymer (globalide + ε-caprolactone + poly(globalide-co-ε-caprolactone)) and a fixed mass ratio of dichloromethane to globalide + ε-caprolactone + poly(globalide-co-ε-caprolactone), of 1:1, were studied. To simulate a polymerization reaction of ε-caprolactone + globalide to poly(globalide-co-ε-caprolactone) different monomers to copolymer conversions (1.25, 2.50, 3.75 and 5.00%) were analyzed. Phase transition of vapor-liquid bubble point (VLE-BP), in a pressure range from 6.31 to 12.58 MPa, and liquid-liquid (LLE), in a pressure range from 10.49 to 26.50 MPa, are reported, together with the lower critical solution temperature (LCST) behavior observed for the systems investigated. The pressure of the systems varied from 6.31 MPa to 26.50 MPa.